High-field asymmetric waveform ion mobility spectrometry for xylene isomer separation assisted by helium-chemical modifiers. Issue 45 (15th November 2022) - Du, Xiaoxia; Wang, Yifei; Zeng, Hongda; Zeng, Hao; Chen, Zhencheng; Li, Hua
Abstract : We propose a combined helium-chemical modifier method for a faster and more convenient separation and detection of xylene isomers. The method employs high-field asymmetric waveform ion mobility spectrometry to investigate the separation and identification of three xylene isomers. This study introduces a novel concept and method for the separation and identification of xylene isomers. Abstract : We propose a combined helium-chemical modifier method for a faster and more convenient separation and detection of xylene isomers. The method employs high-field asymmetric waveform ion mobility spectrometry (FAIMS) to investigate the separation and identification of three xylene isomers. A homemade hollow needle-ring ion source was used, and five chemical modifiers, represented by methanol, ethanol, acetone, ethyl acetate, and acetic acid, were doped into the xylene target analytes to observe the separation and identification of the three isomers. This was based on the fact that the addition of helium and the increase of the RF voltage could no longer improve the resolution of the field asymmetric waveform ion mobility spectrometry system. The experimental results at an RF field voltage of 15 kV cm −1 showed that the spectral peak shifts of o -, m -, and p -xylene in a normal nitrogen environment were −0.21, −0.21, and −0.24 V, respectively. o -Xylene showed a spectral peak of −1.33 V after the addition of helium; however, the separation was not evident. The FAIMS spectrum of xylene showed multiple cluster ion peaks upon addition of the chemical modifiers on top of helium. The alcohol chemical modifiers caused three spectral peaks, with the best effect for methanol, and the characteristic ion peak positions of −7.16, −6.90, and −6.01 V for o -, m -, and p -xylene, respectively. The separation using proton-based chemical modifiers was confirmed to be stronger than that using non-proton-based chemical modifiers, and appropriate volume fractions of chemical modifiers provided a better separation of the target analytes. This study introduces a novel concept and method for the separation and identification of xylene isomers.